PERMAINAN KARTU QUARTET TOKOH UNTUK MENINGKATKAN MOTIVASI BELAJAR SANTRI KELAS XI DI MA - Azril Syamsurizal; Ari Khusumadewi (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2022)
This research arises from the many problems of learning motivation, thus causing a decrease in the level of achievement and interest in students' learning. This encourages researchers to produce products in the form of a quartet card game media as an effort to increase students' learning motivation that meets the feasibility aspect. The research method used is Research and Development (R&D), using the model from Borg and Gall which is carried out until the fifth stage. These stages are, (1) research and data collection, (2) planning, (3) product draft development, (4) initial field trials, and (5) revising the test results. From the assessment of the material test, it got a score of 89.70% which is included in the very good category and does not need to be revised. From the media test, it got a score of 96.42% which was included in the very good category, it did not need to be revised. From the test, prospective users get a score of 96.66% which is included in the very good category and does not need to be revised. Based on these results, the Quartet Character Card product is a good product and the criteria do not need to be revised. So the Character Quartet Card product is ready to be carried out for field testing.